Developing the coastal plain of the Arctic National Wildlife Refuge : joint hearing before the Subcommittee on Environmental Protection and the Subcommittee on Superfund, Ocean, and Water Protection of the Committee on Environment and Public Works, United States Senate, One Hundred Second Congress, first session, May 10, 1991. - United States. Congress. Senate. Committee on Environment and Public Works. Subcommittee on Environmental Protection.; United States. Congress. Senate. Committee on Environment and Public Works. Subcommittee on Superfund, Ocean, and Water Protection. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., Congressional Sales Office, U.S. G.P.O., 1991)
Shipping list no.: 91-547-P. Distributed to some depository libraries in microfiche. Mode of access: Internet.